Exploring Student Perceptions on the Use of English Language Video to Enhance Vocabulary at Secondary School - Gatri, Indira Lailiyah; Safriani, Afida; Salim, Agus (ICONELT, 2024)
Exploring Students' Perceptions Regarding the Use of English Videos in Learning New Vocabulary, is research to find students' perspectives in using English Videos to learn new knowledge. The sampling method used in this research is quantitative and interviews. Data collection was taken from the results of questionnaires and interviews with MAN Kota Surabaya students via Google Docs. Researchers used Google Docs to take a sample of students who met the requirements. The majority of them have watched English videos and the majority of Man Kota Surabaya students said that English videos were useful as a medium for their English learning to learn students' vocabulary by speaking, listening, reading and writing. This research was analyzed quantitatively based on the facts of students who successfully analyzed learning comprehension with English videos with advantages which would later be constructed in descriptive form. The research results showed that learning English Using English videos has many benefits for MAN students in increasing their vocabulary. The benefits include Students will use various strategies to learn vocabulary while watching videos. Students will use words in the appropriate grammatical form of the language; Students pronounce words that are easily recognized; Students recognize understanding in oral and written form; Students spell words correctly; to develop understanding of English. Teachers can develop comprehension teaching with more flexible time by using English videos.